2015
DOI: 10.1086/680023
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Isolation due to Cascade Reinforcement in Lucania Killifish

Abstract: Reinforcement occurs when behavioral isolation is strengthened between species due to selection against hybridization in sympatry. Mate preferences and their target traits may change in sympatry as a consequence of reinforcement. This can potentially generate further behavioral isolation within species if sympatric populations evolve extreme preferences or traits that cause them to reject individuals from foreign populations as mates or be rejected as mates. This process is known as cascade reinforcement. We m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 63 publications
5
66
0
Order By: Relevance
“…Reinforcement in D. yakuba, therefore, adds to the growing number of examples demonstrating that locally adaptive phenotypes subject to reinforcing selection can have costs outside of regions of sympatry [18][19][20][21][22][23][24]. These examples provide evidence that the pattern of RCD frequently described in cases of reinforcement can be actively maintained by selection acting on 'reinforced' alleles between allopatric and sympatric conspecific populations.…”
Section: (B) Cascading Effects Of Reinforcementmentioning
confidence: 82%
See 1 more Smart Citation
“…Reinforcement in D. yakuba, therefore, adds to the growing number of examples demonstrating that locally adaptive phenotypes subject to reinforcing selection can have costs outside of regions of sympatry [18][19][20][21][22][23][24]. These examples provide evidence that the pattern of RCD frequently described in cases of reinforcement can be actively maintained by selection acting on 'reinforced' alleles between allopatric and sympatric conspecific populations.…”
Section: (B) Cascading Effects Of Reinforcementmentioning
confidence: 82%
“…the 'cascade reinforcement' hypothesis [14,15,17]). Recent work supports this hypothesis and suggests that phenotypes favoured by reinforcing selection in sympatry are often disadvantageous in allopatry [18][19][20][21][22][23]. The types of disadvantages can be diverse; however, because reinforcement frequently acts on traits involved in premating isolation, costs tend to manifest as a reduction in the ability to solicit potential mates when 'sympatric' phenotypes are found in allopatry [18][19][20][21][22]24].…”
Section: Introductionmentioning
confidence: 94%
“…Evolution of reproductive barriers through reinforcement has been studied in a variety of organisms from killifish (Kozak et al. ), frogs (Lemmon ), and plants (Suni and Hopkins ) to several insect species (Noor ; Kronforst et al. ).…”
mentioning
confidence: 99%
“…Evolution of reproductive barriers through reinforcement has been studied in a variety of organisms from killifish (Kozak et al 2015), frogs (Lemmon 2009), and plants (Suni and Hopkins 2018) to several insect species (Noor 1999;Kronforst et al 2007). In Drosophila, sexual isolation has been shown to evolve faster than postzygotic isolation (Coyne and Orr 1997), and PMPZ isolation faster than hybrid inviability but more slowly than sexual isolation (Turissini et al 2018).…”
mentioning
confidence: 99%
“…While patterns of mate discrimination consistent with cascade reinforcement have been demonstrated in several empirical systems (Higgie & Blows, 2008;Hoskin, Higgie, McDonald, & Moritz, 2005;Jaenike, Dyer, Cornish, & Minhas, 2006;Kozak et al, 2015;Nosil, 2007;Saetre & Saether, 2010), much less is known about the conditions under which cascade reinforcement evolves (Fuller, 2016). Theoretical models by McPeek and Gavrilets (2006) and Pfennig and Ryan (2006) found that interactions with other species could alter female preferences to initiate isolation within species, but their models assumed speciation was nearly complete and no gene flow between sympatric and allopatric populations.…”
mentioning
confidence: 99%